2022
DOI: 10.32872/cpe.7495
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of physical exercise on negative affect in borderline personality disorder: A pilot study

Abstract: Background Physical exercise is an evidence-based treatment to reduce symptoms and negative affect in several psychiatric disorders, including depressive, anxiety, and psychotic disorders. However, the effect of physical exercise on negative affect in patients with borderline personality disorder (BPD) has not yet been investigated. In this pilot study, we tested the safety, acceptability, and potential acute effects on negative affect of a single session of aerobic physical exercise in adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Furthermore, it has been established as both an effective and cost-efficient intervention for a wide spectrum of psychological issues, encompassing anxiety disorders and depression (14,15). Scholarly research has deduced a notable correlation between physical activity and reduced occurrences of mental ailments (such as depression, stress, negative emotions, and overall psychological distress) and heightened psychological wellbeing (including self-image, life satisfaction, well-being, and mental health) (16)(17)(18). Moreover, the COVID-19 pandemic has triggered extensive psychological challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been established as both an effective and cost-efficient intervention for a wide spectrum of psychological issues, encompassing anxiety disorders and depression (14,15). Scholarly research has deduced a notable correlation between physical activity and reduced occurrences of mental ailments (such as depression, stress, negative emotions, and overall psychological distress) and heightened psychological wellbeing (including self-image, life satisfaction, well-being, and mental health) (16)(17)(18). Moreover, the COVID-19 pandemic has triggered extensive psychological challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, PA was also found efficient in preventing and reducing risk factors of obesity, cardiovascular diseases, and diabetes in individuals with mental disorder (Vancampfort et al, 2013). However, only one study to our knowledge analyzed the short-term effect of PA on BPD itself (St-Amour et al, 2022). No study examined the barriers, preferences and pattern of PA in adults with BPD as reported in a recent review (St-Amour, Cailhol, et al, 2021; St-Amour et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in research for PA in individuals with BPD. However, to our knowledge there are very few observational studies (St-Amour et al, 2023) and only one experimental study (St-Amour et al, 2022) addressing this topic. To develop well-adapted PA interventions for adults with BPD in the future, we need to identify the most important factors associated with adherence.…”
Section: Introductionmentioning
confidence: 99%